Alkaloids from the Sponge‐Associated Fungus Aspergillus sp.1. Issue 5 (11th December 2012) - Zhou, Yaming; Debbab, Abdessamad; Mándi, Attila; Wray, Victor; Schulz, Barbara; Müller, Werner E. G.; Kassack, Matthias; Lin, WenHan; Kurtán, Tibor; Proksch, Peter; Aly, Amal H.
Abstract: Seven new alkaloids including tryptoquivaline K (1 ) and fumiquinazolines K–P (2–7 ), bearing a rare 1‐aminocyclopropane‐1‐carboxylic acid residue, together with six known compounds (8–13 ), were isolated from the fungus Aspergillus sp. obtained from the Mediterranean sponge Tethya aurantium . The structures of the new compounds were determined by extensive analysis by 1D and 2D NMR spectroscopy and mass spectrometry. The absolute configurations of tryptoquivaline K (1 ) and fumiquinazolines K and L (2, 3 ) were determined by TDDFT ECD calculations of their solution conformers, and the configurational assignment of the related fumiquinazolines M–P (4–7 ) was achieved by comparison of their ECD spectra with those of compounds2 and3 . All compounds were evaluated for their cytotoxic activity by the MTT method. Compound8 exhibited pronounced cytotoxicity against the mouse lymphoma cell line (L5178Y) with an IC50 value of 3.6 μM, but only moderate activity was observed against human ovarian cancer (A2780) and human Philadelphia chromosome‐positive chronic myelogenous leukemia (K562) cell lines with IC50 values of 18.5 and 15.0 μM, respectively. Abstract : Seven new alkaloids including tryptoquivaline K (1 ) and fumiquinazolines K–P (2–7 ), bearing a rare 1‐aminocyclopropane‐1‐carboxylic acid residue, together with six known compounds, were isolated from the sponge‐associated fungus Aspergillus sp. The structures of the new compounds were assigned by spectral analysis, and their absolute configurations were determined by calculations.